2011
DOI: 10.1111/j.1365-2648.2011.05809.x
|View full text |Cite
|
Sign up to set email alerts
|

Education and support needs of the older adult with congenital heart disease

Abstract: We have reported that high levels of anxiety and depression in an older population of patients with congenital heart disease are associated with poorer quality of life. This highlights the need to routinely assess anxiety and depression in this patient group and to provide psychological support appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
2
12
0
4
Order By: Relevance
“…15, 16 Interview studies showed that patients' unique psychosocial functioning is caused by parental overprotection, excessive physical restrictions, and uncertain prognoses. These factors may hinder independence and social skills development, and they could also lead to a lack of self-confidence and of self-control.…”
mentioning
confidence: 99%
“…15, 16 Interview studies showed that patients' unique psychosocial functioning is caused by parental overprotection, excessive physical restrictions, and uncertain prognoses. These factors may hinder independence and social skills development, and they could also lead to a lack of self-confidence and of self-control.…”
mentioning
confidence: 99%
“…HADS) noted the following results: in both a British study 29 (patients' mean age was 37.2) and an Iranian study 10 (mean age was 33.2), 13% and 38.3% (26.3% in our study) of ACHD patients, respectively, were probable anxiety cases, and 5% and 17.9% (5.3% in our study), respectively, were probable cases of depression. An Australian study 30 focusing on adolescent patients with heart disease (mean age was 16; 90% diagnosed with CHD) showed that 10% were probable anxiety cases and 3% were probable cases of depression.…”
Section: Discussionmentioning
confidence: 73%
“…Os estudos revisados, em sua grande parte, analisavam principalmente as Karademas, Zarogiannos, & Karamvakalis, 2010;MacInnes, 2013;MacInnes, 2014;McCabe, Barnason, & Houfek, 2011;Molloy et al, 2009;Mulligan et al, 2012;Riley et al, 2012;Schroeder et al, 2012;Steca et al, 2013a;2013b), um estudo foi realizado no continente Asiático (Yan et al, 2011) Mulligan et al, 2012;Schroeder et al, 2012;Steca et al, 2013b). Um outro estudo também utilizou uma escala (Self-Efficacy Scale) para medir os fatores de risco cardíaco (Steca et al, 2013a).…”
Section: Resultsunclassified
“…Quanto à dimensão duração da doença, houve associação entre as crenças na duração cíclica da doença com menor índice de funcionamento físico e mental e menor qualidade de vida (Riley et al, 2012). Em um outro estudo, maiores crenças na duração cíclica da doença se relacionaram com níveis mais elevados de incapacidade funcional e sintomas depressivos três meses após a cirurgia (Juergens et al, 2010).…”
Section: Resultsunclassified
See 1 more Smart Citation